PENERAPAN ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN DI PENGADILAN NEGERI PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - NIA SARI SIHOTANG (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The principle of justice quick, simple and low cost has been regulated in Law Number 48 Year 2009 regarding Judicial Power which replaced Law No. 35 of 1999 on the Amendment of Act No. 14 of 1970 which in Article 4 (2) states, that the judiciary helps seekers of justice and attempt to overcome all the barriers and obstacles in order to achieve the justice that is simple, fast and inexpensive. However, in practice the application of these principles is still a question whether it has been implemented or not, because they in fact often the accumulation of matter and overlapping cases from the previous year. Based on this fact, there are two formulation of the problem in writing this essay, namely: First, How the application of the principle is simple, quick and inexpensive in Pekanbaru District Court based on Law Number 48 Year 2009 regarding Judicial Power? Second, What Factors affecting the application of the principle is simple, quick and inexpensive in Pekanbaru District Court based on Law Number 48 Year 2009 regarding Judicial Power?The research method in this study is a qualitative research method with empirical juridical or sociological research. The data source supported by the primary and secondary data sources. Data collection techniques used were interviews and review of the literature. After the data collected then analyzed qualitatively, and concludes with the deductive method of thinking is to analyze the problems of the general form into special shapes.From the results of research and discussion can be concluded that the application of the principle is simple, fast and low cost in the District Court of Pekanbaru Based on Law No. 48 Year 2009 on Judicial Power is still not going according to what the Law No. 48 Year 2009 concerning Judicial Authority despite various strategies and efforts have been implemented by the District Court of Pekanbaru in order to realize the justice that is simple, fast and inexpensive, but the implementation of the principle is simple, fast and low cost has not yet been able to materialize that can be seen from the number of the settlement that takes a long time that in the end impact on the simplicity and cost of the administration of justice, while the factors that affect the application of the principle is simple, fast and low cost in the District Court of Pekanbaru Based on Law No. 48 Year 2009 on judicial power, among others, is the factor of human resources, a factor of facilities and infrastructure, a factor the number of cases, the complexity of the factors of the case, the means of proof of readiness factor, communication factor in the trial, law enforcement agencies factors that are running the trial, case management factors, factors Act.Keywords: Application - Principle - Simple - Fast - Cost Lightweight - Justice